2021
DOI: 10.1016/j.ymgme.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity of brain MRI patterns in mitochondrial aminoacyl-tRNA synthetase mutations

Abstract: Background and purpose: Mitochondrial aminoacyl-tRNA synthetases-encoded by ARS2 genes-are evolutionarily conserved enzymes that catalyse the attachment of amino acids to their cognate tRNAs, ensuring the accuracy of the mitochondrial translation process. ARS2 gene mutations are associated with a wide range of clinical presentations affecting the CNS. Methods: Two senior neuroradiologists analysed brain MRI of 25 patients (age range: 3 d-25 yrs.; 11 males; 14 females) with biallelic pathogenic variants of 11 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Our study and three other studies (11,12,13) reported a total of 4 patients with hypoparathyroidism, which enhancing the spectrum of endocrine system clinical manifestations. The most accepted pathophysiological mechanism of hypothalamicpituitary axis dysfunction is associated with endocrine glands' high energy demands; impaired mitochondrial ATP production and/or oxidative stress may greatly reduce the ability to secrete hormone or maintain normal feedback (15).…”
Section: Discussionsupporting
confidence: 60%
“…Our study and three other studies (11,12,13) reported a total of 4 patients with hypoparathyroidism, which enhancing the spectrum of endocrine system clinical manifestations. The most accepted pathophysiological mechanism of hypothalamicpituitary axis dysfunction is associated with endocrine glands' high energy demands; impaired mitochondrial ATP production and/or oxidative stress may greatly reduce the ability to secrete hormone or maintain normal feedback (15).…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, another nonsense variant in the same case, Trp520*, is a similar truncation event to the frameshift variant Val499Glyfs*14 in present case. 10 Conversely, a Pro67Ser homozygote was also reported with similar neurological manifestations, it should be noted that codon 67 is still proximal to aminoacyl‐tRNA synthetase domain. 9 As it is characterized by the domain functions, mutations in the catalytic aminoacyl‐tRNA synthetase domain likely affect the essential translation fidelity.…”
Section: Discussionmentioning
confidence: 95%
“… 7 , 8 From 2018 to 2021, eighteen individuals with pathogenic variants in IARS2 gene have been noted with a wide clinical spectrum. 9 , 10 , 11 Among 26 reported patients from nineteen families with differing ethnic backgrounds, 15 patients (58%) have neurologic manifestations, 12 patients (46%) have Leigh disease, 7 , 9 , 10 , 11 , 12 4 patients (15%) have West syndrome, 9 , 11 4 patients (15%) have sideroblastic anemia, 9 3 patients (12%) have cardiomyopathy, 9 , 12 and 3 patients (12%) have isolated cataract. 13 However, approximately 27% of the patients with pathogenic variants in IARS2 have CAGSSS spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…For example, damaging biallelic variants in HARS2 and LARS2 cause Perrault syndrome, an autosomal recessive disorder characterized by sensorineural deafness in both males and females, and ovarian dysgenesis in affected females ( Pierce et al, 2011 ; Pierce et al, 2013 ). While there remains much to learn about these disorders, the fact that biallelic defects in mitochondrial aaRS enzymes do not all lead to identical phenotypes suggests that the underlying disease mechanisms might involve alterations in non-canonical ‘moonlighting’ function rather than solely defects in aminoacylation ( Roux et al, 2021 ).…”
Section: Human Diseases Associated With Genetic Variants In Aars-enco...mentioning
confidence: 99%